Violence and the Maternal in the Marquis de Sade - Clack, Beverley (Feminist theology, 2009)
Feminist philosophers of religion have drawn attention to desire as a neglected category for approaching the sources and concerns of religion. This paper extends this discussion by engaging with one particularly disturbing aspect of the writings of the Marquis de Sade. In a world where ultimate sexual pleasure is derived from destruction of the Other, Sade glories in describing the suffering of mothers, often at the hands of their own children. This paper offers one possible reading of these dark desires through employing aspects of psychoanalytic theory to suggest that, rather than isolate him from the majority of humanity, we might consider possible connections between the desires he details and our own. This involves considering the ambivalence of the mother, and thus challenging the (often oppressive) idealization of the all-caring, all-nurturing mother.